1989
DOI: 10.1159/000177527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acarbose on Serum Lipoproteins in Healthy Individuals during Prolonged Administration of a Fiber-Free Formula Diet

Abstract: The effects of the disaccharidase inhibitor acarbose on serum lipoprotein lipid concentrations were investigated in healthy subjects during prolonged feeding of a fiber-free formula diet. Acarbose was shown to decrease cholesterol and fasting triglyceride concentrations, whereas the postprandial increment of triglycerides was not diminished. The response of fasting triglycerides to acarbose treatment appeared to be related to dietary fat intake, but not to the drug-induced reduction of postprandial glucose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…To explain the cholesterol reduction in healthy young men during acarbose treatment, enhanced bile acid excretion in the small intestine is proposed [14]. Furthermore, by delaying the digestion of polysaccharides, acarbose is capable of increasing the fecal shortchain fatty acid excretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…To explain the cholesterol reduction in healthy young men during acarbose treatment, enhanced bile acid excretion in the small intestine is proposed [14]. Furthermore, by delaying the digestion of polysaccharides, acarbose is capable of increasing the fecal shortchain fatty acid excretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, Walter-Sack et al 83 concluded that, in patients fed with a fibre-free formula diet, acarbose reduced total cholesterol, LDL cholesterol and fasting triglyceride concentration. Reaven et al 84 showed that acarbose lowered plasma triglyceride concentrations (2.4±0.1 to 2.1±0.1 mM, p<0.01) in individuals with poorly controlled T2DM (n=12).…”
Section: Surrogate End Pointsmentioning
confidence: 99%